Reducing food loss and waste: Five challenges for policy and research - Cattaneo, Andrea; Sánchez, Marco V.; Torero, Máximo; Vos, Rob (Elsevier, 2021)
Despite broad agreement in circles on the need to reduce food loss and waste (FLW), considerable gaps in information still exist. This paper identifies policy-relevant information gaps, summarizes recent research that tries to fill these gaps and identifies five challenges for researchers, policymakers and practitioners in reducing FLW. The five challenges identified are: (i) measuring and monitoring FLW, (ii) assessing benefits and costs of FLW reduction and the tradeoffs involved, (iii) designing FLW-related policies and interventions under limited information, (iv) understanding how interactions between stages along food value chain and across countries affect outcomes of FLW reduction efforts, (v) preparing for income transitions and the shifting relative importance of losses and waste as economies develop.